Smart Waste Management System With Internet Of Things - Lee, Soon Chong (Universiti Sains Malaysia, 2018)
Garbage collection is a process of gathering or taking away domestic waste from neighbourhood or town by the authority in charge. The traditional way of collecting garbage is by moving a truck from house to house to take away the household disposal. The collection is usually scheduled in a daily basis or twice a week. However, problem arises when some of the family do not have any domestic waste to be collected or the dustbin still has a sufficient space for garbage dumping. With the traditional method, the garbage collecting truck will move on to collect domestic waste from residential areas as usual without considering the necessity of the process. Therefore, it can cause wastage of man power and fuel. Apart from that, the traditional waste collection cannot ensure the cleanliness of a city or town to be kept all the time. This is because the garbage collecting process only happens in accordance to the schedule. Highly trafficked areas face a situation where the dustbins are filled up quickly and cause overflow. Increased urbanization comes around with higher garbage disposal rate. Hence, the fixed schedule for collection is less efficient. This project presents a waste management system with Internet of Things (IoT) technique. Authority in charge of garbage collection is able to monitor the level of garbage filling through website and smartphone application. When the capacity of the dustbin reaches a certain level and about to overflow, the webpage and smartphone application show an indication to the users and they will be notified that garbage collection is required. The location of the dustbins is shown on Google Map in the webpage. Hence, the authority can view the optimized path for garbage collection. Analysis is done to determine the suitable IoT protocol and hardware for the project. In this system, ultrasonic sensor and weight sensor are implemented to detect the garbage filling of dustbin and Global Positioning System (GPS) module is used to obtain the location of the dustbin. Raspberry Pi 3 acts as the microprocessor and central control unit. Android application is developed by using MIT App Inventor while Python script is employed to program the Raspberry Pi 3 and configure IoT protocol. PHP, HTML, CSS and Javascript are used to perform webpage design. Overall, Internet of Things technique is applied to the system and tested.